Impact of coating and grooving on mechanical performance of bamboo-reinforced concrete - Md Mahmud Siddique; Md Shariful Islam; Md Arifuzzaman (Hybrid Advances)
This study pioneers the synergistic effects of surface coating and mechanical grooving on bamboo-reinforced concrete. Bambusa balcooa strips were treated with 6 % boric acid and coated with water sealer. In compression, plain bamboo strips increased compressive strength by 40 % over unreinforced concrete, but coating slightly reduced this gain. Coated grooved specimens exhibited the highest compressive toughness. In flexure, coated grooved bamboo achieved 222 % higher flexural toughness than unreinforced concrete, with grooving significantly improving flexural strength (9.25 % increase in coated grooved vs. grooved without coating) and modulus (67.44 % higher). The combined treatment optimized interfacial bonding and energy absorption, as confirmed by failure analysis. These findings establish bamboo-reinforced composites as sustainable, high-performance alternatives for construction, with coated grooved bamboo offering unprecedented toughness enhancement.